2018
DOI: 10.1074/jbc.ra118.003831
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dysfunction of human variants of the IRAK4 kinase and a role for its kinase activity in interleukin-1 receptor signaling

Abstract: Interleukin-1 receptor (IL1R)-associated kinase 4 (IRAK4) is a central regulator of innate immune signaling, controlling IL1R and Toll-like receptor (TLR)-mediated responses and containing both scaffolding and kinase activities. Humans deficient in IRAK4 activity have autosomal recessive primary immune deficiency (PID). Here, we characterized the molecular mechanism of dysfunction of two IRAK4 PID variants, G298D and the compound variant R12C (R12C/R391H/T458I). Using these variants and the kinase-inactive D32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
3
32
0
1
Order By: Relevance
“…Receptor engagement has been shown to induce K63-linked polyUb chains on several subunits of the Myddosome, suggesting that this type of modification may be of particular importance in this pathway 92 . Because IRAK4 provides structural integrity to the Myddosome, it is possible that IRAK4 kinase activity-dependent and activity-independent mechanisms work in parallel to facilitate cytokine production downstream of the Myddosome 76 , 93 , 94 . Therefore, further characterization of post-translational modifications of IRAK4 may yield kinase-independent and cell-specific mechanisms of signalling.…”
Section: Irak1 and Irak4mentioning
confidence: 99%
“…Receptor engagement has been shown to induce K63-linked polyUb chains on several subunits of the Myddosome, suggesting that this type of modification may be of particular importance in this pathway 92 . Because IRAK4 provides structural integrity to the Myddosome, it is possible that IRAK4 kinase activity-dependent and activity-independent mechanisms work in parallel to facilitate cytokine production downstream of the Myddosome 76 , 93 , 94 . Therefore, further characterization of post-translational modifications of IRAK4 may yield kinase-independent and cell-specific mechanisms of signalling.…”
Section: Irak1 and Irak4mentioning
confidence: 99%
“…However, all groups found only a modest defect in the degradation of IκBα, and although reduced, NF‐κB activation was still observable . More recently, using highly specific IRAK4 inhibitors 2 independent groups also showed that NF‐κB and MAPK signaling was mostly intact following TLR1/2, TLR4, and IL‐1R activation in the absence of IRAK4 kinase activity in human and mouse myeloid cells . Indeed, an alternative MAPK kinase kinase 3 (MEKK3)‐dependent (TAK1‐independent) pathway has been shown to elicit NF‐κB responses in the absence of IRAK4 kinase activity downstream of TLR activation .…”
Section: The Main Players In Early Myd88‐dependent Tlr Signalingmentioning
confidence: 99%
“…Importantly, a patient with an arginine to cysteine substitution at position 12 (R12C) of IRAK4 suffered from recurrent pyogenic bacterial infections similar to the IRAK4‐deficient patients . The R12C mutation has also further been shown to disrupt IRAK4 interacting with MyD88 in vitro …”
Section: Our Current Understanding Of the Myddosomementioning
confidence: 99%
“…Among the .4000 total cysteines quantified by isoTOP-ABPP in Cal-1 cells, cysteine 13 (C13) of IL-1R-associated kinase IRAK4 stood out as being among the most sensitive to DMF. Noting that C13 resides proximal to the interface involved in MyD88 binding (25) and adjacent to a site of mutation in IL-1R-associated kinase (IRAK) 4 (R12C) implicated in human immunodeficiency 26, we proceeded to show that DMF disrupts both IRAK4-MyD88 interactions and IRAK4-mediated TNF-a production in a C13dependent manner. Taken together, our data indicate that DMF modifies C13 of IRAK4 in human pDCs, and this reaction disrupts MyD88 binding and IRAK4 function.…”
mentioning
confidence: 99%